ANTIDEPRESSANT ACTIVITY OF METHANOLIC EXTRACT OF VERBENA OFFICINALIS LINN. PLANT IN MICE - Jawaid, Talha; Aman Imam, Syed; Kamal, Mehnaz (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: The objective was to investigate the antidepressant activity of methanolic extract of leaves of Verbena officinalis Linn. (MEVO) in mice. Methods: The present study evaluates the antidepressant activity of MEVO in mice using the tail suspension test (TST) and forced swimming test (FST). Their influence on spontaneous locomotor activity (SLMA) was also studied in mice. The MEVO (100 mg/kg, p.o. and 200 mg/kg, p.o.) was administered orally in TST, FST and SLMA for 7 successive days in separate groups of Swiss mice. Results: The extract at 100 and 200 mg/kg, p.o. were able to decrease the immobility time of mice doseâ€dependently when subjected to both tail suspension and forced swim tests and the effects are comparable to that of control group. These results demonstrated that MEVO had specifically antidepressant effects. Conclusion: The present study suggested that MEVO possessed potential antidepressant effects which could be of therapeutic interest for using in the treatment of patients with depression. Keywords: Verbena officinalis Linn., Antidepressant activity, Forced swim test, Tail suspension test, Spontaneous locomotor activity.